PENGUKURAN KINERJA REKSADANA SAHAM TERHADAP HARGA KOMODITAS MENGGUNAKAN BESARAN ALPHA JENSEN DAN CAPM - Robinsyah Anggalis Prasetiyo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This study aims to analyze the stock mutual funds that have the best performance and provide an overview to investors about stock mutual funds can be bought by investors. The research methodology used is a quantitative method with the type of time series data and data sources derived from secondary data obtained from the Indonesia Stock Exchange. The research period from 2012 to 2016. Data analysis techniques used are using the Jensen model which explains that the performance of Mutual Funds can be seen from the amount of alpha of each Mutual Fund with the provisions that if a Mutual Fund has a positive alpha means it has good performance, vice versa Funds with negative alpha indicate poor performance. The results of this study indicate that the performance of Coal, Gold, Nickel and Crude Oil on Equity Funds that manage Capital, Kapital Plus, and Consumption Plus mutual funds products based on the Jensen method each produces insignificant alpha and Jensen alpha values. This means that the performance of mutual funds Kapital, Kapital Plus, and Consumption Plus are not affected by the ups and downs of prices of Coal, Gold, Nickel and Crude Oil.